2005
DOI: 10.1016/j.bbamem.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of bovine serum albumin on membrane lipid peroxidation induced by iron chelate and superoxide

Abstract: Albumin is supposed to be the major antioxidant circulating in blood. This study examined the prevention of membrane lipid peroxidation by bovine serum albumin (BSA). Lipid peroxidation was induced by the exposing of enzymatically generated superoxide radicals to egg yolk phosphatidylcholine liposomes incorporating lipids with different charges in the presence of chelated iron catalysts. We used three kinds of Fe3+-chelates, which initiated reactions that were dependent on membrane charge: Fe3+-EDTA and Fe3+-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…The mutual protection against oxidation between lipid and protein are well known [41][42][43]. In this study, we also found that different forms of iron induced BSA oxidation were inhibited by lecithin liposome (Figs.…”
Section: Discussionmentioning
confidence: 53%
“…The mutual protection against oxidation between lipid and protein are well known [41][42][43]. In this study, we also found that different forms of iron induced BSA oxidation were inhibited by lecithin liposome (Figs.…”
Section: Discussionmentioning
confidence: 53%
“…For example, the antioxidant activities of aromatic amino acids such as In plants and animals, the major water-soluble protein fraction is formed by albumins (Damodaran, 1996). In the literature, the antioxidant activities of albumins from legumes, such as broad beans, white and brown beans and light peas (Okada & Okada, 1998;Wolosiak & Klepacka, 2002) and bovine and human serum (Aime et al, 2003;Fukuzawa et al, 2005;Kouoh et al, 1999;Wolosiak & Klepacka, 2002), have been well documented. The emulsifying and foaming activity of animal and plant origin albumins has also been reported by different workers (AlMalah et al, 2000;Burnett et al, 2002;Damodaran, 1996;Ma & Harwalkar, 1984;Pearce & Kinsella, 1978;Tong, Sasaki, McClements, & Decker, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The DO concentration decrease could be due to whey proteins. In fact, Fukuzawa et al (2005) demonstrated the antioxidant effect of bovine serum albumin which is due amongst others to the trapping of active oxygen molecules. Consequently, proteins probably also interfere on the modulation and stability of DO concentration as well as on the ORP during storage.…”
Section: Storage Of Electroreduced Milkmentioning
confidence: 99%